Does the consumer trust you? - McMahon-Beattie, Una (Henry Stewart Talks, 2009)
Revenue management, pricing and the importance of trust in healthy buyer seller relationships, Definition and general benefits of trust in business, Consumer reaction to variable pricing, Fairness and revenue management, Revenue management and customer relationship management, Customer to customer interaction and breaches of privacy, Recent research into the impact of variable pricing on consumer trust, Importance of rule familiarity, Managerial implications